A angústia e o objeto a na obra de Edgar Allan Poe - Brito, Rafael Ângelo de Oliveira (2019)
It is proposed, in this research, to analyze the work of Edgar Allan Poe from the reading and review of his productions, with the aim of investigating how his work teaches about the aesthetic effect in his relations with anguish and the object a. This investigation arises from a previous research that made it possible to articulate the real and the object a with terror through the link with anguish as the desired affect in this type of fiction. For this, the trail left by Lacan follows, where from the artist's creation material and his attempt at representation, something appears as a remainder, as intimate with what insisted on a resistance to representation and, still, with regard to his way of working with art and his original way of putting it in relation to reality. Freud's formulations about anguish make up, in this path, a central axis of this investigation. An exponent of a tradition whose literary marks remain today, Poe is taken as an object of study, in particular, for the place he occupied in Lacan's teaching. Starting from this possible treatment given by art to reality, in its relations with anguish, we investigate what type of procedure is highlighted in Poe's work, taking as its starting point the Fatal Woman and the strange object present in his work. Furthermore, the effect that, against the will of the Self, therefore against the will of its own sense, is provoked in the reader by this object and which denounces the very cause of artistic creation, is essential in his writings. In Poe's tales, the treatment given to the female figure and the appearance of a foreign object in the plot are observed, thus opting for the tales to provide a production closer to what we want to delimit as an object, without refraining from bringing contributions sporadic of his poetry. It starts with the look and the voice as pulsating objects that guided the listening of Poe's writing and the relationship between these and the anguish was more precisely delimited, guided by the psychoanalytic texts that deal with the anguish and the object a. The tales indicate forms of the subjects' relationship with this archaic element (object a) and that will trigger the anguish for maintaining an intrinsic association with the primordial subjective loss. What causes strangeness, whether in the voice of the first story, in the look of Ligeia in the second or in the teeth extracted from the third, is the positive character that it establishes in the face of what should not appear, since it constitutes a subjective loss since the your origin. It is pointed out, here, something that appears in the place that should be empty and the relationship of this emergence with anguish and the effect connected to the stranger.